Hepatic Organoid-Based High-Content Imaging Boosts Evaluation of Stereoisomerism-Dependent Hepatotoxicity of Stilbenes in Herbal Medicines - Juan Liu; Tingting Li; Ruihong Li; Jie Wang; Pengyan Li; Ming Niu; Le Zhang; Chunyu Li; Tao Wang; Xiaohe Xiao; Jia-bo Wang; Jia-bo Wang; et al. (Frontiers Media S.A., 2022)
The complexity of chemical components of herbal medicines often causes great barriers to toxicity research. In our previous study, we have found the critical divergent hepatotoxic potential of a pair of stilbene isomers in a famous traditional Chinese herb, Polygonum multiflorum (Heshouwu in Chinese). However, the high-throughput in vitro evaluation for such stereoisomerism-dependent hepatotoxicity is a critical challenge. In this study, we used a hepatic organoids-based in vitro hepatotoxic evaluation system in conjunction with using high content imaging to differentiate in vivo organ hepatotoxicity of the 2,3,5,4'-tetrahydroxy-trans-stilbene-2-O-β-glucoside (trans-SG) and its cis-isomer (cis-SG). By using such an organoid platform, we successfully differentiated the two stereoisomers' hepatotoxic potentials, which were in accordance with their differences in rodents and humans. The lesion mechanism of the toxic isomer (cis-SG) was further found as the mitochondrial injury by high-content imaging, and its hepatotoxicity could be dose-dependently inhibited by the mitochondrial protective agent. These results demonstrated the utility of the organoids-based high-content imaging approach in evaluating and predicting organ toxicity of natural products in a low-cost and high-throughput way. It also suggested the rationale to use long-term cultured organoids as an alternative toxicology platform to identify early and cautiously the hepatotoxic new drug candidates in the preclinical phase.